2008
DOI: 10.1128/iai.01514-07
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Uses Multiple Mechanisms To Acquire the Essential Metabolite Inositol during Infection

Abstract: Candida albicans is an important cause of life-threatening systemic bloodstream infections in immunocompromised patients. In order to cause infections, C. albicans must be able to synthesize the essential metabolite inositol or acquire it from the host. Based on the similarity of C. albicans to Saccharomyces cerevisiae, it was predicted that C. albicans may generate inositol de novo, import it from the environment, or both. The C. albicans inositol synthesis gene INO1 (orf19.7585) and inositol transporter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…The three PCR products were treated with ExoSAP-IT (USB Corp.) to remove contaminating primers and deoxynucleotide triphosphates (dNTPs) and then combined in a 1:3:1 molar ratio (5ЈCNA1 NCR -SAT1 flipper-3ЈCNA1 NCR ) to generate the disruption allele by overlap PCR using flanking primers JC61/JC62 (ϳ100 bp closer to the CNA1 ORF compared with JC57/JC60, respectively, reserving primers JC57/JC60 for further integration confirmation), resulting in an ϳ6-kb 5ЈCNA1 NCR -SAT1 flipper-3ЈCNA1 NCR CNA1 disruption allele. The first allele of the CNA1 gene was disrupted in the wild-type strain CD36 by transformation with 0.2 to 1 g of gel-purified disruption DNA by electroporation (17). Two independent heterozygous nourseothricin-resistant mutants (YC31 and YC29; Table 1) were obtained from two separate transformations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three PCR products were treated with ExoSAP-IT (USB Corp.) to remove contaminating primers and deoxynucleotide triphosphates (dNTPs) and then combined in a 1:3:1 molar ratio (5ЈCNA1 NCR -SAT1 flipper-3ЈCNA1 NCR ) to generate the disruption allele by overlap PCR using flanking primers JC61/JC62 (ϳ100 bp closer to the CNA1 ORF compared with JC57/JC60, respectively, reserving primers JC57/JC60 for further integration confirmation), resulting in an ϳ6-kb 5ЈCNA1 NCR -SAT1 flipper-3ЈCNA1 NCR CNA1 disruption allele. The first allele of the CNA1 gene was disrupted in the wild-type strain CD36 by transformation with 0.2 to 1 g of gel-purified disruption DNA by electroporation (17). Two independent heterozygous nourseothricin-resistant mutants (YC31 and YC29; Table 1) were obtained from two separate transformations.…”
Section: Methodsmentioning
confidence: 99%
“…Radiolabeled probes were generated using the Rediprime-it kit (Stratagene) and [␣-32 P]dCTP (Easy Tides; Perkin-Elmer, Boston, MA). Ultrahyb buffer (Ambion) was used for prehybridization at 42°C, and hybridization and washing conditions were as described previously (17). Radioactive signals were exposed onto the storage phosphor cassette and digitalized with a Typhoon 9200 phosphorimager (Molecular Dynamics).…”
Section: Methodsmentioning
confidence: 99%
“…The seven members of group I (Itr1, Itr1a, Itr2, Itr3, Itr3a, Itr3b, and Itr3c) share strong sequence homology with well-characterized ITR genes in other fungi, such as S. cerevisiae and C. albicans. Group II has three members (Itr4, Itr5, and Itr6) that are more distantly related ITR genes that have been characterized in other yeasts but are closely related to HGT19, potential a second ITR in C. albicans (12). However, the role of HGT19 in inositol function has not yet been confirmed.…”
mentioning
confidence: 99%
“…Inositol can also be imported from the extracellular environment via inositol transporters. The inositol transporter (ITR) gene family is part of the sugar transporter superfamily and plays an important role in inositol sensing in fungi, including Saccharomyces cerevisiae (30,31,(42)(43)(44)51), Candida albicans (12,28,50), C. neoformans (64), and Schizosaccharomyces pombe (40). Studying ITR genes in fungi has clinical significance as ITR genes identified in lower eukaryotes, such as fungi (28) and protozoa (15,39,52), are proton coupled and differ both kinetically and pharmacologically from the sodium-dependent inositol transporter system (SMIT) in humans.…”
mentioning
confidence: 99%
“…In vivo studies carried out with gene fused to this promoter have also revealed that the promoter is not induced to any significant extent in vivo (32,33). This suggests that the yeasts do not face a sulfur starvation in vivo, at least in the mouse model of systemic candidiasis.…”
Section: Discussionmentioning
confidence: 96%